PERAN KEUNGGULAN BERSAING SEBAGAI VARIABEL YANG MEMEDIASI KEMAMPUAN INOVASI DAN ENTREPRENEURAL MARKETING PADA KINERJA PEMASARAN (Studi Pada Umkm Makanan Dan Minuman Di Provinsi Jawa Tengah) - Hadi, Arman; Utaminingsih, Adijati; Kuswardani, DC (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2023)
This study aims to analyze the role of competitive advantage as a variable moderating innovation capability and entrepreneurial marketing on the marketing performance of food and beverage SMEs in Central Java. Problems caused by declining MSME marketing performance around the Covid-19 pandemic. This study was conducted using a quantitative research approach and analyzed using SmartPLS 3. The population of this study is the SMEs in the catering industry in Central Java Province, including a total of 100 SMEs, and the sample is determined by simple random sampling. The results of the analysis show that innovation capability, entrepreneurial marketing, and competitive advantage have positive and significant effects on marketing performance. Competitive Advantage